2021
DOI: 10.2196/23311
|View full text |Cite
|
Sign up to set email alerts
|

The Uncounted Casualties of a Hidden COVID-19 Epidemic in China: Cross-sectional Study on Deaths Related to Overwork

Abstract: Background During the COVID-19 response, nonclinical essential workers usually worked overtime and experienced significant work stress, which subsequently increased their risk of mortality due to cardiovascular diseases, stroke, and pre-existing conditions. Deaths on duty, including deaths due to overwork, during the COVID-19 response were usually reported on web-based platforms for public recognition and solidarity. Although no official statistics are available for these casualties, a list of on-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The COVID-19 pandemic has created an unprecedented crisis ( 1 ). The first wave of the COVID-19 epidemic in China was brought under control with 3 months—from mid-January 2020 (when human-to-human transmission of COVID-19 was confirmed) to the end of March 2020 ( 2 ). COVID-19 was recognized as a Class B infectious disease by National Health Commission, and was treated as a Class A infectious disease for prevention and control on January 20, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has created an unprecedented crisis ( 1 ). The first wave of the COVID-19 epidemic in China was brought under control with 3 months—from mid-January 2020 (when human-to-human transmission of COVID-19 was confirmed) to the end of March 2020 ( 2 ). COVID-19 was recognized as a Class B infectious disease by National Health Commission, and was treated as a Class A infectious disease for prevention and control on January 20, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Although the National Assembly passed legislation in February 2018 to shorten work hours, with the revised law to be applied on an annual basis depending on the size of the workplace [ 41 ], more data is needed to evaluate the effectiveness of this policy. As the COVID-19 pandemic resulted in social restrictions and heavier workloads on the workforce, many researchers [ 42 , 43 , 44 ] have suggested that the increased workload among health professionals resulted in health problems such as increased levels of stress, depression, anxiety, physical exhaustion, as well as increased rates of CCVDs. While it should not be ignored that health professionals are at increased risk of infection with COVID-19, it is also essential to recognize that professionals in other fields have also been overworked during the COVID-19 pandemic, emphasizing that teleworking leads to constant overworking [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…difficulty in accessing services, changes in health priorities 54 including lifestyle and adherence changes, possibly difficulty of paying for prescriptions) and system factors (e.g. telehealth-5855 and reduced opportunity for follow-up in-person with patients in which medications can be discussed, perhaps concern about some drugs interacting with COVID, perhaps focus on other health areas for overworked professionals during pandemic, 56 , 57 etc.).…”
Section: Discussionmentioning
confidence: 99%